The impact of reward on employees motivation at Petronas Penapisan Melaka / Fazillahaslizah Ab.Rahim - Ab.Rahim, Fazillahaslizah (Faculty of Business and Management, 2011)
Employees are one of the company assets that are very important in order to achieve organization goals. Therefore many companies believe that it is important to make sure that their company are happy and satisfy with the reward and other variable given by the company. Employees motivation is important to many companies because it gives impact on the employees productivity, effectiveness and efficiency. The main objectives of this research is to identify the most factors that influence employees motivation among employees of PETRONAS Penapisan Melaka and to identify the significant relationship between independent variable (payment, promotion, recognition and benefits ) and dependent variable (employees motivation ).